Attention-Deficit Hyperactivity Disorder-Like Traits and Distractibility in the Visual Periphery. (June 2017) - Panagiotidi, Maria; Overton, Paul G.; Stafford, Tom
We examined the performance of nonclinical subjects with high and low levels of self-reported attention-deficit hyperactivity disorder (ADHD)-like traits in a novel distractibility paradigm with far peripheral visual distractors, the likely origin of many distractors in everyday life. Subjects were tested on a Sustained Attention to Response Task with distractors appearing before some of the target or nontarget stimuli. When the distractors appeared 80 ms before the targets or nontargets, participants with high levels of ADHD-like traits were less affected in their reaction times than those with lower levels. Reducing the distractor-target or nontarget interval to 10 ms removed the reaction time advantage for the high group. We suggest that at 80 ms, the distractors were cueing the arrival of the target or nontarget, and that those with high levels of ADHD-like traits were more sensitive to the cues. Increased sensitivity to stimuli in the visual periphery is consistent with hyperresponsiveness at the level of the superior colliculus.